The Fluid Management Experience in Patients with Chronic Kidney Disease Undergoing Hemodialysis in Indonesia: A Qualitative Study - Mailani, Fitri; Muthia, Rahmi; Herien, Yelly; Huriani, Emil; Chan, Chong Mei; Abdullah, Khatijah Lim (Department of Nursing, Faculty of Medicine, Diponegoro University, 2021)
Background: Fluid management can reduce mortality, severe comorbidities, and debilitating symptoms in patients on hemodialysis. Therefore, a restricted fluid intake plan is crucial for patients with chronic kidney disease (CKD). Little evidence has been found to date on exploring the experience in fluid management of CKD patients in Indonesia.Purpose: This study aimed to explore the fluid management experience of adults with chronic kidney disease participating in hemodialysis treatment in Indonesia.Methods: A qualitative study with a phenomenological approach was conducted. Purposive sampling was used to recruit 14 adults patients with chronic kidney disease undergoing hemodialysis in a tertiary hospital in Padang between July and September 2020. Manual content analysis using the Colaizzi approach was used to identify themes.Results: Data analysis revealed four themes with 12 sub-themes. The four major themes include the challenge of thirst control, fluid/diet restriction management, inadequate information, and the support system.Conclusions: The result showed the severe suffering and sadness experienced by CKD patients who conform to fluid restrictions. It is important to provide clear information on the fluid prescription or the exact consumable amount per day. Structured education with a personal approach is recommended to ensure detailed information regarding